Da cólera ao acontecimento junho de 2013: do que escapa à representação em Deleuze e Lacan - Venera, José Isaías (2017)
Investigate the language emploied under vertigo in the protests in June 2013. Movement that presents itself as a cholera time, expressed in the force that mobilizes the crowd in the protests. Therefore, the title "From anger to the rebellion of desire in the June 3013 event: from what escapes the representation in Deleuze and Lacan". To account for this initial problem, to work with what eludes representation and at the same time, this force-significant in the June 2013 event, there is initially the concepts of Real, in Jacques Lacan, and virtual, in Gilles Deleuze. Force that appears in this thesis as problematic object: a stranger who insists, always to return. It starts with the language and its relationship with the representation and the simulacrum as power without template for the second time, working with two concepts that allow us to analyze the strange object in the June 2013 event, ie the quasi-cause deleuzian and the object to Lacanian. This initial arrangement, which (anti) method is the concept of rhizome, is initiated the analysis of sources, divided into three records: the saying; the look; and for the voice. The saying is evidenced both speech acts of demonstrators in the act of escape from the discursive framework of journalists when the very discourse of corporate media from the materials and expert analysis in the search than ever fails, that is, to summarize the events in a possible narrative of closing the meaning, of interpreting the facts without leaving loose ends. The look is already occupy another record and subject's position, now composing the crowd framed the lens of the photographic evenly matched or moving image capture. Following is the speech dispersed the crowd that is lost to make pressing the voice. To account for the voice as invoking drive, or voice as escape expression, amateur videos are taken as material issues for analysis. The words of a member of the Free Pass Movement stand out as the expression of this strange object: "Note there, I am nobody." The view, the Ceci n'est image pas vingt cents, frame retelling This is not a pipe, René Magritte, calls into question the model of representation and for which there will be the beginning of a series of images that operate as schize look. Finally, the proliferation of speeches, divulged in videos produced during the protests, point to the emergence of the voice as the opening of the senseless. The analyzes follow two theoretical assumptions, the philosophy of Deleuze and the psychoanalysis of Lacan, but from these two authors, a new theoretical scene opens to a certain extent following the marked field by Alain Badiou, anti-philosophy, or, perhaps best score as the authors who, on the trail of Nietzsche, seeking to reverse Platonism, which is why the notion of simulacrum gains a certain relevance in this work and for which stands out the critique of the notion of representation. The protests of June 2013 are analyzed in what remains in them as an event, that is, what is not allowed to be symbolized. Apart from this movement of dwelling on what escapes representation, it is important to underscore the notion of interval subject as an effort to interpret the gesture of life that characterizes the contemporaneity. The subject that emerges in the gap between images projected on the black screen of mobile gadgets, as smartphones. When the black screen is activated again after a long time consuming images, a track of the subject is repeated – a spectral image – that soon disappears when it exits the interval.